«Sincerely yours, The children of Miraflores and San Miguel» - Mendívil Trelles de Peña, Luzmila (2014)
This article presents the results of a research developed during the course «Education and Social Harmony», from early childhood teachers specialty, which was offered from August to December 2013 by the Faculty of Education from thePontifical Catholic University from Peru (PUCP). The field work was in charge oftwenty three early childhood students. The study was delimited as an action ofsocial responsibility. It has as a premise to show the different points of view that children have from their districts. The study was developed in six early childhood institutions from Metropolitan Lima, three of them belong San Miguel district,and the rest from Miraflores district. The choices were made by Municipality staffs and the total of kids that were asked their opinions were four hundred fifty three (four to five years old). The article reflects the voice of these children, their dreams, and opinions from their cities which are fundamental not only for district improvement, but as a way of social learning that stimulates the inclusion and participation of all citizens and promotes the democratic harmony.